MENELISIK PEMANFAATAN KECERDASAN BUATAN TERHADAP MINAT BACA SISWA SMA NEGERI 1 MUARO JAMBI - Dera Firanda; Johi Kasih; Rahmatunissa; Siti Enik Mukhoiyaroh Bambang; Wahdania Nur Rahmayani; Sri wahyuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Along with the development of the times, the world has produced many innovations in the field of digital technology, one of which is Artificial Intelligence (AI), which has already been utilized by students, particularly those at SMA Negeri 1 Muaro Jambi. This research aims to discuss three research focuses, namely the reading interest of students at SMA Negeri 1 Muaro Jambi; the frequency of AI usage in the learning process; and students' perspectives on AI. This study uses a descriptive research type with a qualitative approach. The subjects of the research are students of SMA Negeri 1 Muaro Jambi, and the research objects are students' reading interests and the frequency of AI usage. The data sources in this study consist of primary data obtained directly from 31 students of SMA Negeri 1 Muaro Jambi. The data collection technique in this research was conducted through the distribution of online questionnaires to the students of SMA Negeri 1 Muaro Jambi via WhatsApp chat groups. The research results indicate that the reading interest of students at SMA Negeri 1 Muaro Jambi is at a fairly good level, although it has not yet shown a strong tendency. In addition, the majority of respondents stated that they utilize AI to search for information related to their study materials. Lastly, regarding students' perspectives on AI, it was found that AI is seen as a useful learning aid, but it has not entirely replaced the role of reading in obtaining valid and in-depth information. Based on the overall findings, AI influences the way students access and process information more than it reduces reading interest, and therefore cannot be regarded as the main cause of low reading interest among students. It is hoped that strengthening the literacy culture should be balanced with digital literacy so that the use of AI can support, rather than replace, reading habits.